Hubungan Pengetahuan, Sikap Dan Pola Pemberian Makan Terhadap Kejadian Stunting Pada Balita 12-59 Bulan Di Desa Sukamulya Kecamatan Cugenang : The Relationship between Knowledge, Attitudes and Feeding Patterns on the Incident of Stunting in Toddlers 12-59 Months in Sukamulya Village, Cugenang District - Nurianti, Risma (Indonesian Scholar Journal of Nursing and Midwifery Science, 2024)
Introduction: Stunting is a condition of failure to thrive in children under five years of age due to chronic malnutrition which results in short children compared to other children of their age. Mother's nutritional knowledge affects a person's food consumption. People who have good nutritional knowledge will have the ability to apply nutritional knowledge in food selection and processing so that their food intake is more secure and able to pay attention to good nutrition for children and their families. The purpose of this study was to determine the relationship between knowledge and attitudes and feeding patterns with the incidence of stunting in Sukamulya Village, Cugenang District in 2023. Methods: This research is an observational study with a cross-sectional design. Height measurements and data collection were carried out in July-August 2023. The population in this study were all children under five in Sukamulya Village, Cugenang District in 2023. The sample in this study was 82 children under five. Respondents in this study were mothers of toddlers in Sukamulya Village, Cugenang District, as many as 82 people. Results: The results of the study were obtained from 82 respondents it was found that mothers who had good knowledge were as many as 75 people (91,5%), mothers who had a positive attitude were 76 people (92,7%) mothers who had healthy eating patterns. well as many as 70 people (85,4%) and there were 77 children (93,9%) not stunted. And the results of the chi-square analysis test for the category of knowledge of mothers with stunting events obtained a p-value = 0,000 (p = < 0,05); while for the category of attitudes of mothers with stunting events obtained a p-value = 0,000 < (0,05); and while for the category of mother's feeding parenting pattern with stunting incident obtained p-value = 0,001 < (0,05). Discussion: The conclusion in this study is that there is a relationship between knowledge and attitudes and feeding patterns with the incidence of stunting in Sukamulya Village, Cugenang District in 2023.